2016
DOI: 10.1002/rcs.1741
|View full text |Cite
|
Sign up to set email alerts
|

A zero phase adaptive fuzzy Kalman filter for physiological tremor suppression in robotically assisted minimally invasive surgery

Abstract: The ZPAFKF can provide less error, preferred accuracy, better tremor estimation, and more desirable compensation performance, to suppress hand tremor and decrease vibration at the surgical instrument tip. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…To verify the proposed algorithm, a master–slave minimally invasive surgical robotic system including a master manipulator, a slave manipulator and a control system has been developed, which is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To verify the proposed algorithm, a master–slave minimally invasive surgical robotic system including a master manipulator, a slave manipulator and a control system has been developed, which is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Some vibration suppression methods have been studied by researchers, but they mainly focused on physiological hand tremor suppression by using modern digital filters . In our previous research, a zero phase adaptive fuzzy Kalman filter (ZPAFKF) was proposed to alleviate physiological hand tremor, and the experimental results also showed that physiological tremor was not the only factor that led to vibration of the slave manipulator and the surgical instrument . The slave manipulator is usually moved with low speed motion, the rotational speed of each joint is less than π/3 rad/s and translational velocity is less than 30 mm s −1 (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 30 years, minimally invasive surgery (MIS) has significantly impacted surgical techniques across various specialties and has nearly supplanted traditional open surgery. Nonetheless, MIS presents two primary drawbacks: an extended learning curve for minimally invasive procedures and the challenge of addressing the surgeon's hand tremors, which can significantly impact intraoperative bleeding and postoperative recovery [1,2]. Since the birth of the Automated Endoscopic System for Optimal Positioning (AESOP) as the first FDA-certified auxiliary surgical robot in 1994, various types of surgical robot systems have sprung up like mushrooms.…”
Section: Introductionmentioning
confidence: 99%